Strategi Pengembangan Tenun Ikat Kupang Provinsi Nusa Tenggara Timur - Budiana Setiawan; R.R. Nur Suwarningdyah (Jurnal Pendidikan dan Kebudayaan, 2014)
The purpose of this research was to review strategies used by craftsmen and role of local government in the effort to develop Kupang ikat woven in Kupang Municipality, East Nusa Tenggara. The method used in this research included: observation at Kupang ikat woven workshop, in-depth interviews with resource people such as artisans, entrepreneurs, and local government; study of literatures; and focus group discussion. The result of the research represented that the strategies undertaken by craftsmen for developing the Kupang ikat wovens are started from cheap raw material supply and easy to obtain; diversification of products; development of manufacturing technology; increasing the organizational management, and marketing effort to increase better product. In order to implement the strategies successfully, the craftsmen shall have to get support and training from the local government. Through the Institution of Industry and Trade, the support for the craftsmen given in several activities, i.e. workshop; assistance of equipment production; credit for capital, involvement in exhibitions; guidance to have patent, and increase the affection of people to the crafts of the region. The challenge for the craftsmen in developing the Kupang ikat woven were the limited of fund, difficulty to gain raw materials and marketing.